Sistem Aplikasi Kearsipan Akademik Dosen Bahasa Arab Berbasis Online - Saleh, Nalahuddin; Sopian, Asep; Maulani, Hikmah; Khalid, Shofa Musthofa (Ilmu Informasi Perpustakaan dan Kearsipan, 2024)
The progress of human life is influenced by the development of science and technology. The rapid development of information technology today in the current era of globalization cannot be avoided anymore its influence on the world of education. Archive management in universities is very important because from the archives created, all aspects of the activities that occur in the college are illustrated. However, archive management that aims to tidy up activity data actually raises problems or obstacles, one of which is the opportunity to lose lecturer data archives both related to education, research, community service and other supporting elements. The purpose of this research is to have an application program for online-based lecturers' academic archives. This study uses research and development methods. To meet this goal, a Quality Information System was created https://sim-arabupi.com which is a web-based information system that manages the internal data of the Arabic Language Education Department.